Science identity trajectories throughout school visits to a science museum. Issue 5 (20th November 2019) - Shaby, Neta; Vedder‐Weiss, Dana
Abstract: Research has repeatedly demonstrated how informal learning environments afford science‐identity development by fostering a broader array of interactions and recognizing more varied participation modes and roles, as compared to the classroom. Thus, science teachers are encouraged to take students to field trips in informal environments, including science museums. However, the question of whether and how informal environments indeed support science identities also in a schooling context (i.e., in field trips) has not yet been explored. This case study addresses this question by analyzing identity trajectories of three students throughout six school visits to an Israeli science museum. We observed and recorded these students in the museum over the course of 3 years (fourth to sixth grade). We also visited their school and interviewed them after each visit. Drawing on a sociocultural interactional approach to identity, we analyzed 18 hr of video and audio recordings, tracking the participation of the three students across time and contexts, comparing between the students, points in time and settings, including structured (museum lab), semi‐structured (riddle‐solving activities in exhibition halls), and unstructured settings (free exploration). We employed linguistic ethnographic methods and microanalysis to examine the ways in which the students participated and their positioning by self and others. While we found differences between settings within the museum, overall, the findings show that the museum reproduced the school's interaction, positioning, and roles. The "(non)science person" in school was also the "(non)science person" in the museum, and thus, the museum visits did not appear to shift identity trajectories. These findings challenge the premise that informal environments support the development of science identities also in a schooling context and call for a more critical view of such fieldtrips in terms of their pedagogical and physical design, facilitation approach, and consideration of peers' social interaction.